2019
DOI: 10.1111/jomf.12620
|View full text |Cite
|
Sign up to set email alerts
|

Tied and Troubled: Revisiting Tied Migration and Subsequent Employment

Abstract: Objective: This article looks at couples' migration decision making processes and their gender-specific employment consequences after migration to Germany. Background: International migration has evolved into a common experience for couples around the globe. Previous research has focused on the internal migration of couples and families. This article is the first to consider couples' international migration decisions drawing on the theoretical concepts of Mincer's tied migration theory and gender role beliefs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 44 publications
2
23
0
Order By: Relevance
“…Another important gender consideration for partnered immigrant women's employment is their migration order, though to our knowledge, few studies investigate this in the European context. Krieger (2019) shows that both male and female lead immigrants enter the German labor market earlier than their tied (or equal) counterparts, but only male lead immigrants benefit in a higher employment probability. Thus, the gender imbalance in the selection into tied migration likely contributes to the gender gap in outcomes on the new labor market (if they choose to enter at all) (Krieger 2019).…”
Section: Gender Gap Among Immigrantsmentioning
confidence: 96%
“…Another important gender consideration for partnered immigrant women's employment is their migration order, though to our knowledge, few studies investigate this in the European context. Krieger (2019) shows that both male and female lead immigrants enter the German labor market earlier than their tied (or equal) counterparts, but only male lead immigrants benefit in a higher employment probability. Thus, the gender imbalance in the selection into tied migration likely contributes to the gender gap in outcomes on the new labor market (if they choose to enter at all) (Krieger 2019).…”
Section: Gender Gap Among Immigrantsmentioning
confidence: 96%
“…Often it is assumed that women who immigrate for family reasons have a very low motivation to enter the labour market. While several studies have shown that this is indeed the case (Ballarino & Panichella 2018;Basilio, Bauer & Sinning 2009;Krieger 2020), it should also be acknowledged that channels of migration to Germany are heavily restricted for immigrants from certain origins. For example, even for economically motivated migrants from outside the EU, the only option to legally enter Germany may be as a family migrant.…”
Section: Theoretical Framework and Existing Findingsmentioning
confidence: 99%
“…For some aspects of integration, such as employment and German language proficiency, retrospectively provided, pre-migration data is also available. This allows for analysis of changes in migrants' lives since their arrival in Germany (Krieger 2020b).…”
Section: Research Potentialsmentioning
confidence: 99%